The Effect of Employee Empowerment and Work Stress on Employee Organizational Commitment Mediated by Job Satisfaction (Case Study of Financial Services Cooperatives in Denpasar) - I Gede Suriadnyana (Magister Manajemen, Program Pascasarjana, Universitas Warmadewa, 2020)
A cooperative is a business entity owned and operated by an individual for the benefit of members. The business outgrowth is aligned with the small-medium business expansion in the local area, Bali as general. The objectives of this study are to examine the effect of employee empowerment, job stress, organizational commitment, job satisfaction at the Financial Services Cooperative in Denpasar and to examine the role of job satisfaction in mediating the effect of employee empowerment on organizational commitment at the Financial Services Cooperative in Denpasar. The data for this study conducted from representable cooperatives in Denpasar based on the criteria of a minimum asset, and Good cooperate governance score, this researched collected 63 numbers of respondents by random sampling method. This study is implemented qualitative and quantitative research by spreading the questionnaire to the respondence and also interviewed after the respondence filled up the questionnaire, Partial least square (PLS) has been used as hypothesis testing. The results of this study show that (1). Employee empowerment process is effect positively significant to job satisfaction for the cooperatives employment, (2). Work field pressure has a positive effect on job satisfaction, (3). Work field pressure is positive but insignificantly effect to the organizational commitment, (4). Job satisfaction is showing positive insignificant effect toward the organizational commitment, (5). This research found that mediation factor between commitment and employee empowerment is work satisfaction.